1973
DOI: 10.1073/pnas.70.6.1768
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Direction of Replication of Bacteriophage 186 DNA

Abstract: Intracellular bacteriophage 186 DNA replicates as a single-branched circle during the first round of replication. The free end of the branch is located at a unique position with respect to phage 186 DNA base sequence, and this point should, therefore, correspond to the origin of DNA replication. The position of the growing point has been mapped at various degrees of replication, and found to move unidirectionally from left to right with respect to the denaturation map of phage 186 DNA.A small proportion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1974
1974
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Interestingly, in a BLAST 2 alignment with the P2 A gene, the rep gene of K139 was found to be 90% identical to a small region of the A gene (30 bp), which corresponds to the mapped origin of replication in P2. The same region of K139 rep is also 94% identical to a small sequence of the A gene of phage 186 (data not shown), which is also in good accordance with the location of the 186 ori estimated by electron microscopy studies (10). The conservation of this small region suggests the same location for the ori sites within these phages and could possibly reflect a common binding specificity for the related replication proteins.…”
Section: Resultssupporting
confidence: 71%
“…Interestingly, in a BLAST 2 alignment with the P2 A gene, the rep gene of K139 was found to be 90% identical to a small region of the A gene (30 bp), which corresponds to the mapped origin of replication in P2. The same region of K139 rep is also 94% identical to a small sequence of the A gene of phage 186 (data not shown), which is also in good accordance with the location of the 186 ori estimated by electron microscopy studies (10). The conservation of this small region suggests the same location for the ori sites within these phages and could possibly reflect a common binding specificity for the related replication proteins.…”
Section: Resultssupporting
confidence: 71%
“…Because the available evidence indicates that the chromosomes of OX, P2, and 186 replicate unidirectionally (2,10,25), we investigated whether the E. coli rep chromosome replicates unidirectionally as would be the case if one of the growing forks in the bidirectionally replicating chromosome required the rep function. We found that although the rep chromosome is, in fact, replicated in a bidirectional manner from an origin in approximately the same position as in rep+, there are some interesting alterations in the structure of the replicating chromosome.…”
mentioning
confidence: 99%
“…for 10 min and then banded in a Cs gradient (12 When the h strand of Hy dis was used, the structures were also as predicted in Fig. 2; their distribution is shown in Table 1 with the exception of the ambiguous heteroduplexes).…”
Section: Methodsmentioning
confidence: 97%
“…point (Fig. 3A) and were thought to result from branch migration of the growing point (12,14,15). The combined length of the two strands was used in the plot of branch lengths (Fig.…”
Section: Methodsmentioning
confidence: 99%